IMPLEMENTASI PRINSIP KERJA SAMA DALAM EKONOMI SYARIAH PADA INDUSTRI PENGASINAN IKAN TRADISIONAL DI PULAU PASARAN BANDAR LAMPUNG - Mawardi Mawardi (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the implementation of cooperation principles in Islamic economics within the traditional salted fish processing industry in Pulau Pasaran, Bandar Lampung City. The research focuses on the forms and mechanisms of cooperation practiced and their alignment with Islamic economic principles, particularly justice, mutual assistance (ta’awun), trustworthiness (amanah), and risk-sharing. A descriptive qualitative approach was employed, with data collected through in-depth interviews, observation, and documentation involving actors in the salted fish processing industry. The findings reveal that cooperation practices remain informal and rely heavily on personal trust, without clear contractual agreements. Although Islamic economic values are culturally embedded through solidarity and honesty, their implementation has not been institutionally structured. Profit and risk-sharing mechanisms tend to be disproportionate, resulting in unequal relationships between capital owners and workers. These findings indicate a gap between the normative ideals of Islamic economics and empirical practices in traditional industries. The study concludes that strengthening Islamic economic literacy, business mentoring, and the establishment of fair and transparent cooperation mechanisms are essential to promote sustainable implementation of Islamic economic cooperation principles in traditional industrial sectors.